1970
DOI: 10.1083/jcb.46.2.354
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationships in the Adipose Cell

Abstract: Serum albumin stimulates the uptake of U-glucose-14C and the incorporation of 14C-counts into triglyceride glycerol and inhibits the incorporation of 14C-counts into triglyceride fatty acids by isolated adipose cells; insulin and epinephrine enhance these effects. In the absence of hormones, these responses to albumin increase with increasing albumin concentration. In the presence of insulin, a qualitatively similar pattern of increasing responses to albumin is observed; the enhancement of each response by ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

1971
1971
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
2
13
0
2
Order By: Relevance
“…Actual basal cpm i4C02 released by cells treated with or without 1% albumin was similar (637 vs. 607). Repeated insulin dose-response tests in our laboratory confirmed these similarities and were in accord with other studies [8] in which insulin-stimulated l4C incorporation into CCK triglycerides and fatty acids were not affected by the pres ence or absence of albumin in the media. This shows that the absence of albumin in the media does not affect over all fat cell metabolism.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Actual basal cpm i4C02 released by cells treated with or without 1% albumin was similar (637 vs. 607). Repeated insulin dose-response tests in our laboratory confirmed these similarities and were in accord with other studies [8] in which insulin-stimulated l4C incorporation into CCK triglycerides and fatty acids were not affected by the pres ence or absence of albumin in the media. This shows that the absence of albumin in the media does not affect over all fat cell metabolism.…”
Section: Discussionsupporting
confidence: 78%
“…Values are mean ± SEM of three separate assays, each performed in duplicate. reported to influence the uptake of glucose by isolated adipocytes by increasing COy evolution in presence of epinephrine, stimulating triglyceride and inhibiting fattyacid synthesis and enhancing the release of nonesterified fatty acids from cpinephrinc-trcatcd cells [8],…”
Section: Introductionmentioning
confidence: 99%
“…From these data they inferred an increased rate of cellular lipolysis and postulated that this might lead to insulin resistance. Theoretically, this possibility receives some support from the recent observations of Nestel and Whyte indicating that the rate of lipolysis is increased in the obese (25) and of Cushman and Rizack who have reported that intracellular free fatty acid influences the metabolism of adipose cells (26). However, the studies of Di Girolomo and Rudman do not exclude the possibility that these metabolic alterations in glucose metabolism are the result of adipose cellular insulin resistance rather than the cause, and that loss of insulin sensitivity may be due to some other cellular derangement.…”
Section: Discussionmentioning
confidence: 68%
“…30-40 mg of tissue, removed by surgical biopsy, were incubated in plastic vials for 2 h at 37'C in 2.0 ml KrebsRinger bicarbonate buffer containing 40 mg/ml untreated bovine serum albumin (Bovine Albumin Powder, Fraction (21). On occasion, the distribution of ["C]glucose carbons between the glycerol and fatty acid moieties of the extracted lipid was analyzed by the method described by Rodbell (22) and modified by Cushman and Rizack (23). All results have been expressed as micrograms glucose carbon incorporated into C02 and glyceride-glycerol or fatty acid/cell per h, calculated as previously reported (3).…”
Section: Methodsmentioning
confidence: 99%